Artificial Metalloenzymes Constructed From Hierarchically‐Assembled Proteins. Issue 8 (22nd May 2013) - Ueno, Takafumi; Tabe, Hiroyasu; Tanaka, Yuya
Abstract The design of artificial metalloenzymes has become an important topic in biological chemistry and inorganic chemistry due to the potential applications of artificial metalloenzymes in nanoscience and biotechnology. One of the general methods used to produce artificially metalloenzymes involves the encapsulation of non‐natural metal cofactors within protein scaffolds. This method has been used in the construction of small artificial metalloproteins with high activity and selectivity. However, the important roles of protein assemblies have not yet been systematically investigated in this field, even though natural enzymatic systems employ protein assemblies as molecular scaffolds for elaborate enzymatic reactions. In recent years, the above‐mentioned general strategy has been applied to functionalize protein assemblies such as protein cages and protein crystals. These assembled structures form confined interior environments, which can be used to accommodate metal complex catalysts and to prepare metal nanoparticles. The development of artificial metalloenzymes with hierarchically‐assembled proteins would enable us to provide powerful tools for industrial and biological applications. In this Focus Review, we discuss the most significant recent research in this field as well as future directions.